2004
DOI: 10.1016/s0899-3467(07)60093-7
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Idiopathic Scoliosis Treatment Using Pettibon Corrective Procedures: A Case Report

Abstract: Pettibon corrective procedures seemed to be effective at reducing the thoracolumbar scoliosis 15 degrees (43%) after six weeks. The subjective and objective results of this case study warrant further such investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…An anterior shift in the centre of gravity of the head elicits the head and neck postural reflexes involving the vestibulocollic [21], cervicocollic [22] and cervical-facet mechanoreceptors. These respond to the forward head position of the postural stimulation by actively orienting the trunk's centre of gravity under the head's centre of gravity [23]. Increased trunk flexion with increasing load has been identified as adaptation to bring the centre of gravity of the body and backpack further forward to maintain balance [24].…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…An anterior shift in the centre of gravity of the head elicits the head and neck postural reflexes involving the vestibulocollic [21], cervicocollic [22] and cervical-facet mechanoreceptors. These respond to the forward head position of the postural stimulation by actively orienting the trunk's centre of gravity under the head's centre of gravity [23]. Increased trunk flexion with increasing load has been identified as adaptation to bring the centre of gravity of the body and backpack further forward to maintain balance [24].…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…In a description of a case lasting 4 weeks, Morningstar et al outlined the use of these same therapies in a 20-year-old woman with a 35°right thoracic scoliosis and reported a correction of 15°. 35 At 3 years after treatment, a follow-up radiographic study revealed continued improvement of 18°. 36 Another case series by Morningstar looked at the results of a multimodal chiropractic rehabilitation treatment in adult patients.…”
Section: Manipulation Plus Exercisesmentioning
confidence: 95%
“…35 At 3 years after treatment, a follow-up radiographic study revealed continued improvement of 18°. 36 Another case series by Morningstar looked at the results of a multimodal chiropractic rehabilitation treatment in adult patients. 37 After a 2-year follow-up, the average Cobb angle correction was about 9°across 28 total patients.…”
Section: Manipulation Plus Exercisesmentioning
confidence: 95%
“…1 Curvatures less than 10°are viewed as a variation of normal, as those curves have little potential for progression. 2,3 Idiopathic scoliosis is estimated to affect about 2% to 3% of young females.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Idiopathic scoliosis is estimated to affect about 2% to 3% of young females. 1,[4][5][6] The conventional treatment of a child or an adolescent with idiopathic scoliosis often lasts months or years. 7 Not only does the disease produce a visible deformity of the body, but also the treatment itself may cause psychological stress and induce stress reactions.…”
Section: Introductionmentioning
confidence: 99%